Struktura drzewostanów a populacje cisa pospolitego (Taxus baccata L.) w rezerwatach przyrody „Cisy Rokickie” i „Bogdanieckie Cisy” - Dobrowolska, Dorota; Niemczyk, Marzena; Olszowska, Grażyna (Leśne Prace Badawcze, 2012)
Yew Taxus baccata L. is an endangered tree species in parts of Europe. In Poland small populations grow in forest reserves. The study was conducted in two reserves established particularly for the protection of yew populations located in the region of Pomerania. The aim of the study was to know the number, vitality and growth conditions of natural yew regeneration and to identify threats to the regeneration of the species. The stand structure and regeneration of yew was described in 30 circular plots. The main tree species in stand canopy was Scots pine, however in Bogdanieckie Cisy beech also made up an important element of the stand. The density of yew regeneration was greater in Bogdanieckie Cisy than in Cisy Rokickie; the number of yew seedlings was 5000 individuals per hectare in Boganieckie Cisy and 3332 individuals per hectare in Cisy Rokickie. The vitality of yew regeneration was better under the beech-pine canopy in Bogdanieckie Cisy reserve than in Cisy Rokickie. Yew regeneration is grazed in the Cisy Rokickie reserve even though the fence. The forest floor influenced the amount of yew regeneration; the greater cover of herbs the lower the density of yew regeneration. The presence of yew in all phases (from seedlings to small trees) that regeneration processes continue in both reserves.